Clinical management of finger joint capsulitis/synovitis in a rock climber - Vagy, Jared (Frontiers in Sports and Active Living, 2023)
This case study presents a 23-year-old, male rock climber with finger joint capsulitis / synovitis. During the patient exam the diagnosis was ruled in with clinical orthopedic testing. Additional movement analyses identified faulty gripping mechanics contributing asymmetric finger loading. A comprehensive rehabilitation program was developed based on the concepts of a progressive framework that included unloading the affected tissues, increasing mobility, improving muscle performance, and correcting suboptimal climbing movements. After 6 weeks, the climber’s pain 24 hours after climbing decreased from 5.5/10 to 1.5/10 and at one year follow-up 0/10, his PSFS improved from 0% at the initial evaluation to 43% after 6 weeks, to 98% after one year, and his Sport-Specific DASH improved from 69% to 34% to 6%. He made a full recovery back to his previous grade of V8 bouldering. This is the first case study of its kind to provide a rehabilitation framework for the management of finger joint capsulitis / synovitis in a rock climber.